Effect of Gap Width on the Distance between Bright Patterns in Yellow - Rahmawati, Amalia Darozatun; Ayu Febrianti, Dilla; Faturahman, Faturahman; Malik, Adam (Prodi Fisika FKIP Unram, 2023)
This research aims to determine the effect of gap width on the distance between bright patterns in the yellow color experiment. This research was carried out in a virtual laboratory, with the method used is a quantitative method with an experimental method, namely the method used to determine the effect of the independent variable on the dependent variable. Data collection was taken during the practicum using the PhET website in the Wave Interference – Slits section, with yellow light which has a wavelength of around 670-690 nm. The distance between two slits is 1500 nm and three different slit widths are used, namely 500 nm, 600 nm, and 700 nm. This research shows that the smaller the value of the gap width, the greater the value of the dark light pattern. Where, the wider the gap, the denser the light-dark pattern on the screen, and the smaller the gap width, the more sparse the light-dark pattern on the screen. Keywords: Gap Width; PhET; Dark Light Pattern.